2019
DOI: 10.3390/plants8010014
|View full text |Cite
|
Sign up to set email alerts
|

THROUGH THE LOOKING GLASS: Real-Time Imaging in Brachypodium Roots and Osmotic Stress Analysis

Abstract: To elucidate dynamic developmental processes in plants, live tissues and organs must be visualised frequently and for extended periods. The development of roots is studied at a cellular resolution not only to comprehend the basic processes fundamental to maintenance and pattern formation but also study stress tolerance adaptation in plants. Despite technological advancements, maintaining continuous access to samples and simultaneously preserving their morphological structures and physiological conditions witho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…An earlier study on soil-and sand-grown wheat roots found discoloration, but no algal attachment to the root surface [17]. It is possible and probable that algal cell attachment can cause a certain amount of biotic stress response of wheat and Brachypodium roots [48]. Furthermore, microbial and algal cells are known to produce plant-active effectors such as auxin-like molecules affecting root phenotypes [44].…”
Section: P-form Complexity Within Algae Biomass Offers Potential For ...mentioning
confidence: 99%
“…An earlier study on soil-and sand-grown wheat roots found discoloration, but no algal attachment to the root surface [17]. It is possible and probable that algal cell attachment can cause a certain amount of biotic stress response of wheat and Brachypodium roots [48]. Furthermore, microbial and algal cells are known to produce plant-active effectors such as auxin-like molecules affecting root phenotypes [44].…”
Section: P-form Complexity Within Algae Biomass Offers Potential For ...mentioning
confidence: 99%
“…Many of the microfluidic devices used for studying the rhizosphere share a similar design concept ( Khan et al, 2019 ). They have an opening port, sometimes with pipette tips inserted into the PDMS body where the seed of the seedling rests and a microchannel where the primary root grows into.…”
Section: Next Generation Of Plant Growth Chambersmentioning
confidence: 99%
“…The dimension of the channel depends on the type and age of the plant. For example, an Arabidopsis thaliana’s seedling is typically grown in a microfluidic device up to 10 days, with chamber dimension around 150 to 200 μm in height, whereas the Brachypodium distachyon seedling chamber is 1 mm in height due to its thicker roots ( Massalha et al, 2017 ; Khan et al, 2019 ). Media and/or inoculation of the microbiome is achieved through additional channels to the main chamber.…”
Section: Next Generation Of Plant Growth Chambersmentioning
confidence: 99%
“…The expression profiles of AKR genes in leaves and roots subjected to control conditions, salt, dehydration, and ABA treatments were also investigated, to provide insight into the potential roles of AKRs in the abiotic-stress regulation of plants. Studies have shown that resistant breeding of genes with significant changes in transcription levels under stress may be of great significance [28][29][30]. The main purpose of this study is to explore and identify candidate genes in regulation of salt, drought, and ABA stresses and provide the basis for the further elucidation of the biological function of MtAKRs and their regulation in abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%